Genetic correlation between fetal nuchal translucency thickening and cystic hygroma and exploration of pregnancy outcome - Zheng, Jianli; Wang, Tiantian; Sun, Huilin; Guan, Yongjuan; Yang, Fangfang; Wu, Jing; Ying, Feifei; Fu, Yadong; Li, Min; Liu, Jianbing (Scientific reports, 2024)
Chromosome microarray analysis (CMA) and whole exome sequencing (WES) are increasingly utilized in prenatal diagnosis of abnormal ultrasound findings, but studies on correlation between pathogenic copy number variations (pCNVs) and single-gene mutations in fetuses with nuchal translucency (NT) thickening/cystic hygroma (CH), and pregnancy outcomes, are rare. This study aimed to investigate clinical value of CMA and WES for NT thickening/CH in fetuses, explore genetic correlation between fetal NT thickening and CH, and analyze pregnancy outcomes. We retrospectively selected 215 pregnant women diagnosed with fetal NT thickening (NT > 95th)/CH who underwent invasive prenatal diagnosis at our hospital from January 2020 to June 2022. With negative chromosomal karyotype analysis (KA) and CMA results, patients voluntarily underwent WES. Patients were grouped by NT thickening/CH, and application value of KA, CMA, and WES examined. Ultrasound findings, pregnancy outcomes, and fetal growth post-birth were followed during mid/late pregnancy and post-delivery. Abnormalities in chromosomal number were detected in 28 of 215 samples, with a detection rate of 13.0%, and pCNVs were detected in 12 cases, with a detection rate of 5.6%. The most common abnormality in fetuses from both groups suggested by CMA was 22q11.21 microdeletion-microduplication syndrome. 35 patients with negative KA and CMA results underwent WES, and single gene variants were detected in 12 fetuses, with an abnormality rate of 34.3%. The incidence of adverse pregnancy outcomes was 28.2% in the NT thickening group and 82.9% in the CH group ( P < 0.05 ). Overall, fetal NT thickening/CH was associated with genetic abnormalities, WES further improved the diagnosis of abnormal fetuses after negative KA and CMA results in both groups, and the incidence of adverse pregnancy outcomes was lower in the NT thickening group than in the CH group. The management of pregnancy outcomes could guide clinical genetic counselling.